Waste and residue management: sustainable hospital catering services - Hatice Baygut; Saniye Bilici (Discover Sustainability)
Abstract Objective Hospital catering services, like other food and beverage businesses, have the potential to cause negative environmental impacts. This study aims to analyze the food waste, food residue, and non-food waste calculations of the menus used in hospital catering services. Method The study was conducted in all 4 seasons and 31 day months were included in the study to standardize the number of days of practice in the selection of seasonal menus. In the menus, one of the most frequently produced dishes using traditional production methods was selected separately for lunch and dinner. In the study, food waste, food residue, and non-food waste calculations of pre-selected meals applied in hospital catering services were made. Results In the spring, summer, autumn, and winter seasons, the food waste levels of the one portion for the first group were significantly higher than the food waste levels of the second group and one portion for the third group (p < 0.001). In the summer season, the level of food residue of one portion for the second group was significantly higher than the level of food residue of one portion for the first group (p < 0.05). In all seasons, the levels of non-food waste of one portion for the second group were significantly lower than the levels of non-food waste of the first group and one portion for the third group (p < 0.05). Conclusion Dietitians need to plan menus by adopting sustainable nutrition models. In this context, efforts should be made to plan menus in which local suppliers will be supported and food waste and non-food waste will be reduced. In-service training activities covering strategies and activities to reduce food waste and food residues should be planned for kitchen and service personnel under the leadership of food services and nutrition dietitians.